2014
DOI: 10.3329/pa.v18i2.19197
|View full text |Cite
|
Sign up to set email alerts
|

Problems and Prospects of Fish Fry Trade in Jessore District of Bangladesh

Abstract: A study was conducted to investigate the existing system of fry trade and different problems and prospects associated with this enterprise in Jessore district. A total of 82 hatchery operators and nursery owners were interviewed using a structured questionnaire. In the study period 4211.5 kg hatchling were produced in 85 hatcheries in this area of which 80% were reared in the same area. Average price of per kg hatchling were Indian major carps-Tk.1200 to 1800, Chinese carp Tk. 1200 to 1600 and Thai sharpunti a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Survival rate of fry: According to hatchery operators, the survival rate of the fry during different stages of the rearing process and transportations was more than 95% and as a result the mortality rate was less than 5%. Rahaman et al (2007) found that the fry mortality was 24% due to improper management in Jessore district of Bangladesh which is much more than this finding. The fry of river Halda was more disease resistant and had capacity to adapt with little environmental stressed condition even.…”
Section: Methodsmentioning
confidence: 76%
“…Survival rate of fry: According to hatchery operators, the survival rate of the fry during different stages of the rearing process and transportations was more than 95% and as a result the mortality rate was less than 5%. Rahaman et al (2007) found that the fry mortality was 24% due to improper management in Jessore district of Bangladesh which is much more than this finding. The fry of river Halda was more disease resistant and had capacity to adapt with little environmental stressed condition even.…”
Section: Methodsmentioning
confidence: 76%
“…Above result was relevant with the Sharif and Asif (2015) reported that hatchlings production of Indian major carps were 24,720 kg, Exotic carps were 21754 kg and other species were 2966 kg respectively in 2013 at Jessore sadar. Rahaman (2007) also got that 85 hatcheries in Jessore area were produced 4211.5 kg hatchling at study period of which 80% were reared in the same area.…”
Section: Figure 2 Hatchling Production In Sylhet Districtmentioning
confidence: 83%
“…On the other hand, the lack of capital, lack of transportation facilities was the main problems for nursery owners. Rahaman et al, (2007) also stated that the main constrains were lack of capital (35%) followed by lack of technical knows-how (27%) faced by fry traders. The nursery operators faced the problems like lack of capital (31%), high lease value (25%), high price of production inputs (17%), violence (12%), intense market competition (9%) and the lack of policy support (6%) in Jessore.…”
Section: Figure 12 Problems Faced By Fish Farmersmentioning
confidence: 99%
“…Natural fish seed are collected from different rivers, mainly during the rainy season (May to August) (Haque and Dey, 2017;Rahaman et al, 2007). Jamuna, Padma, Brahmaputra, Gorai-modhumuti, Halda, and Arialkha are the main river systems from where fish seeds are collected (Tab.…”
Section: Production Of Fish Seed From Natural Sourcementioning
confidence: 99%
“…The destruction of fish resources due to indiscriminate capture of brood fish, destruction of spawning ground by cutting the oxbow bend, illegal sands quarrying, and pollution of the river by industrial and agricultural wastes have been a major concern (Alam et al, 2020;Kabir et al, 2015). The increasing seed demand for the growing aquaculture sector and the decrease in seed supply from natural sources led to the establishment of many hatcheries in the country (Islam et al, 2017c;Rahaman et al, 2007). At present, aquaculture is mainly dependent on fish seed produced in hatcheries (Debnath et al, 2020).…”
Section: Production Of Fish Seed From Natural Sourcementioning
confidence: 99%